Konsentrasi Limbah Pencemar MBAS (Methylen Blue Active Substance) pada Perairan Muara Kali Ijo, Kabupaten Kebumen - Dhani, Putri Rizki Rahma; Hendrayana, Hendrayana; Hidayati, Nuning Vita; Haryati, Ani (Fakultas Perikanan dan Ilmu Kelautan, 2023)
Muara Kali Ijo is the place where rivers flow in Kebumen Regency, which carry a lot of domestic wastes resulting from sanitation activities, namely detergent. The study aims to determine the quality of Muara Kali Ijo Waters based on MBAS concentration (Methylen Blue Active Substances). MBAS is a standard method for determining the concentration of anionic surfactants in detergents. This study uses descriptive methods with purposive random sampling techniques. Sampling was carried out on March 11, 2023 with a total of five stations. The results of the analysis of the MBAS concentration in the BBSPJPPI laboratory ranged from 0.031 – 0.064 mg/L and the measurement of water quality parameters was still relatively good, below the quality standard threshold. PCA results show that there is a negative correlation between MBAS concentration and water quality parameters. Productive anthropogenic activities around the area have a potential to contribute detergent waste from washing activities and increase MBAS concentrations. Keywords: antropogenic, muara kali ijo, MBAS, PCA, waters quality